Criminological Analysis of State Crime Based on Game Theory - Nabiollah Gholami; Hussein gholami (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2022)
Explaining new phenomena and events in various fields using macro and interdisciplinary theories and strategies is on of the practical tools for better understanding of these phenomena in order to adopt appropriate management-executive approaches to them. Therefore, understanding the concept of "Sovernment Crime" as a systematic violation of citizens' rights by the government, under "Game Theory" as one of the strategic theories to explain phenomena and events in the fields of social sciences and international relations, is a matter that is both from the perspective of understanding and promotion. The so-called government crime literature is worthy of attention in terms of attention to the objective and practical aspects of identifying and responding to government crimes. Therefore, in this article, considering the state and citizens as two main actors in different fields, and using the principles and elements of game theory, it has been argued that the actors participating in a game have rationality and by calculating their possible profit and loss participate in the game process and seek maximum profit and minimum loss. These actors reach equilibrium at a point known as the saddle point - in which each actor has gained a certain amount of profit and loss. This point is the point where it is no longer possible to receive more profit and less loss for any of the parties, and if the game continues, they will suffer a decrease in profit and an increase in loss. Finally, it has been concluded that the states, with tools such as bringing other actors into their playing field with citizens, using rents and information tools, changing the rules and regulations governing the game, cause the balance to be disturbed and the saddle point to be shifted to turned towards themselves and thus cause systematic violation of citizens' rights.